Cadherin 2-Related Arrhythmogenic Cardiomyopathy: Prevalence and Clinical Features. (10th February 2021) - Ghidoni, Alice; Elliott, Perry M.; Syrris, Petros; Calkins, Hugh; James, Cynthia A.; Judge, Daniel P.; Murray, Brittney; Barc, Julien; Probst, Vincent; Schott, Jean Jacques; Song, Jiang-Ping; Hauer, Richard N.W.; et al.
Abstract : Supplemental Digital Content is available in the text. Abstract : Background: Arrhythmogenic cardiomyopathy (ACM) is an inherited cardiac disease characterized by fibrofatty replacement of the right and left ventricle, often causing ventricular dysfunction and life-threatening arrhythmias. Variants in desmosomal genes account for up to 60% of cases. Our objective was to establish the prevalence and clinical features of ACM stemming from pathogenic variants in the nondesmosomal cadherin 2 (CDH2), a novel genetic substrate of ACM. Methods: A cohort of 500 unrelated patients with a definite diagnosis of ACM and no disease-causing variants in the main ACM genes was assembled. Genetic screening of CDH2 was performed through next-generation or Sanger sequencing. Whenever possible, cascade screening was initiated in the families of CDH2 -positive probands, and clinical evaluation was performed. Results: Genetic screening of CDH2 led to the identification of 7 rare variants: 5, identified in 6 probands, were classified as pathogenic or likely pathogenic. The previously established p.D407N pathogenic variant was detected in 2 additional probands. Probands and family members with pathogenic/likely pathogenic variants in CDH2 were clinically evaluated, and along with previously published cases, altogether contributed to the identification of gene-specific features (13 cases from this cohort and 11 previously published, for a total of 9 probands and 15 family members). Ventricular arrhythmic events occurred in most CDH2 -positive subjects (20/24, 83%), while the occurrence of heart failure was rare (2/24, 8.3%). Among probands, sustained ventricular tachycardia and sudden cardiac death occurred in 5/9 (56%). Conclusions: In this worldwide cohort of previously genotype-negative ACM patients, the prevalence of probands with CDH2 pathogenic/likely pathogenic variants was 1.2% (6/500). Our data show that this cohort of CDH2 -ACM patients has a high incidence of ventricular arrhythmias, while evolution toward heart failure is rare.